EVALUATION OF THE 'INDONESIA GEMILANG' COMMUNITY EMPOWERMENT PROGRAM BY LAZ Al-AZHAR IN CILEMBU VILLAGE - Dwiputrianti, Septiana; Rangkuti, Rina Andriani; Pratiwi, Arundina Dijah Retno; Mursalim, Siti Widharetno (Jurnal EL-RIYASAH, 2024)
This research evaluates the "Indonesia Gemilang" community empowerment program implemented by LAZ Al-Azhar in Cilembu Village, Sumedang Regency. The research aims to analyse the process, impact, and challenges of the program, particularly its contribution to poverty reduction and socio-economic development. The importance of this study lies in its relevance to Public Administration, specifically in addressing local governance, development policies, and public empowerment. The study highlights key factors in achieving successful community development by focusing on the ACTORS theory, which emphasizes authority, competence, opportunity, responsibility, and community support. The methodology employed is qualitative, using a single case study approach, including interviews and field observations. The findings suggest that while the program has positively impacted the local community by increasing self-reliance and economic sustainability, challenges remain, particularly in empowering local leaders to take a more active role in program management and expanding market opportunities for community-produced goods. This research contributes to the field of Public Administration by providing valuable insights into the effective design and implementation of community empowerment programs, offering practical solutions to improve public policy in rural development.